Phylogenetic characterization of Central/Southern European lineage 2 West Nile virus: analysis of human outbreaks in Italy and Greece, 2013–2014. (December 2015) - Barzon, L.; Papa, A.; Lavezzo, E.; Franchin, E.; Pacenti, M.; Sinigaglia, A.; Masi, G.; Trevisan, M.; Squarzon, L.; Toppo, S.; Papadopoulou, E.; Nowotny, N.; et al.
Abstract: In recent years, West Nile virus (WNV) lineage 2 has been spreading and causing disease outbreaks in humans and animals in Europe. In order to characterize viral diversity, we performed full-length genome sequencing of WNV lineage 2 from human samples collected during outbreaks in Italy and Greece in 2013 and 2014. Phylogenetic analysis showed that these WNV lineage 2 genomes belonged to a monophyletic clade derived from a single introduction into Europe of the prototype Hungarian strain. Correlation of phylogenetic data with geospatial information showed geographical clustering of WNV genome sequences both in Italy and in Greece, indicating that the virus had evolved and diverged during its dispersal in Europe, leading to the emergence of novel genotypes, as it adapted to local ecological niches. These genotypes carried divergent conserved amino acid substitutions, which might have been relevant for viral adaptation, as suggested by selection pressure analysis and in silico and experimental modelling of sequence changes. In conclusion, the results of this study provide further information on WNV lineage 2 transmission dynamics in Europe, and emphasize the need for WNV surveillance activities to monitor viral evolution and diversity.